Trends and determinants of crop diversification in Uttar Pradesh - KUMAR, SANJEEV; KUMAR, SHIV; CHAHAL, VED PRAKASH; SINGH, DHARAM RAJ (The Indian Journal of Agricultural Sciences, 2018)
The process of crop diversification towards high-value crops in Uttar Pradesh at regional as well as district level for the period 1990-91 to 2011-12 was examined. Simpson index of diversification and panel data regression analysis were used to analyze the trends and drivers of crop diversification. The results infer that state agriculture is moving from traditional crops to high value crops. This becomes the apt choice of policy makers for boosting agricultural growth. However, this shift is not found evenly distributed across the districts/regions. The irrigation, fertilizers and mechanization were found to be the major drivers of shift in the area towards high value crops and leads to less diversification. On the other hand, access to primary markets has positive impact on diversification. This necessitates the redesign and implementation of different strategies for crop diversification in these regions. The insight emanating from results emphasize not only to arrest the rising intra-regional disparities but also policy support in terms of better marketing infrastructure, easy and cheap access to agricultural credit for the development of irrigation facilities and farm mechanization, availability of fertilizers and appropriate technologies for increasing farm income and improving farmers’ livelihoods.